Compressive loading causes unique mechanism of failure in second generation sliding hip screw. (1st January 2013) - Bethel, Monique; Levenda, Jeffrey; Hogg, Peter; Alge, Daniel; Chu, Tien-Min G.; Mullis, Brian
The sliding hip screw (SHS) has been used for the fixation of intertrochanteric hip fractures for decades. Newer devices have been designed to address persistent failures in SHS; however, the superiority of all new devices has not been established. We compared the stability of a classic SHS to a 2nd generation device. Intertrochanteric fractures were created in cadaveric and synthetic femurs, and then repaired with either a 1st generation SHS or a 2nd generation SHS. Fixation by both implants was tested by compressive loading. There was a significantly higher rate of failure via rotational instability of the proximal fragment (p < 0.05) with the 2nd generation SHS due to disengagement of an anti-rotational bushing mechanism. Further studies are needed to determine if this study translates to concerns for higher failure rates in the clinical setting, however our results suggest that there is no benefit to the use of this 2nd generation device.